2013
DOI: 10.1073/pnas.1216206110
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide scan of healthy human connectome discoversSPON1gene variant influencing dementia severity

Abstract: Aberrant connectivity is implicated in many neurological and psychiatric disorders, including Alzheimer's disease and schizophrenia. However, other than a few disease-associated candidate genes, we know little about the degree to which genetics play a role in the brain networks; we know even less about specific genes that influence brain connections. Twin and family-based studies can generate estimates of overall genetic influences on a trait, but genome-wide association scans (GWASs) can screen the genome for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
128
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 61 publications
2
128
0
2
Order By: Relevance
“…This measure of so-called functional connectivity (FC) [see Friston (2011) for a review] is organized in robust resting-state networks (Beckmann et al 2005;Damoiseaux et al 2006;Moussa et al 2012), and has been used to explore a range of properties such as cognition (Richiardi et al 2011;Heine et al 2012), emotions , and learning (Bassett et al 2011). From an anatomical point of view, structural connectivity (SC) and its multi-scale spatial organization have also been characterized (Sporns et al 2004(Sporns et al , 2005 and linked to brain diseases (Kaiser 2013;Griffa et al 2013;Engel et al 2013) and genetic influences (Jahanshad et al 2013;Ziegler et al 2013). The relationship between SC and FC, and more particularly the way cerebral anatomy shapes neuronal functions is a question that has been addressed ever since neuroimaging techniques allowed to collect both structural and functional information [e.g., McIntosh and Gonzalez-Lima (1994)].…”
Section: Introductionmentioning
confidence: 99%
“…This measure of so-called functional connectivity (FC) [see Friston (2011) for a review] is organized in robust resting-state networks (Beckmann et al 2005;Damoiseaux et al 2006;Moussa et al 2012), and has been used to explore a range of properties such as cognition (Richiardi et al 2011;Heine et al 2012), emotions , and learning (Bassett et al 2011). From an anatomical point of view, structural connectivity (SC) and its multi-scale spatial organization have also been characterized (Sporns et al 2004(Sporns et al , 2005 and linked to brain diseases (Kaiser 2013;Griffa et al 2013;Engel et al 2013) and genetic influences (Jahanshad et al 2013;Ziegler et al 2013). The relationship between SC and FC, and more particularly the way cerebral anatomy shapes neuronal functions is a question that has been addressed ever since neuroimaging techniques allowed to collect both structural and functional information [e.g., McIntosh and Gonzalez-Lima (1994)].…”
Section: Introductionmentioning
confidence: 99%
“…Pilot studies showed that the data could be analyzed in a consistent way (Jahanshad et al 2013a;Kochunov et al 2014). As the ENIGMA3 project involves a cortical volumetric analysis, the current plan is for ENIGMA to use those cortical regions as the basis for a structural connectivity analysis, using the same voxel-wise analysis of the connections as advocated in Stein et al (2010) and Jahanshad et al (2013b). It will be interesting to see if similar sample sizes, tens of thousands, are needed to find and replicate genetic associations with measures of structural brain connectivity.…”
Section: Genetic Screening Of the Connectomementioning
confidence: 99%
“…Structural connectivity and patterns of organization are also influenced by genetic factors. Jahanshad et al (2013b) showed that a fraction of the total number of detected connections are indeed highly heritable, while Bohlken et al (2014) studied the network's topology to establish heritability for other global measures of fiber connections.…”
Section: Genetic Screening Of the Connectomementioning
confidence: 99%